The Devil In Dover an insider's story of dogma v. Darwin in small-town America - Lebo, Lauri; Donated by Rev. Dr. Go Van Mung (New York The New Press, 2008)
Discusses the court battle in Dover, Pennsylvania, involving the right for schools to teach intelligent design in science classes, and includes the political and religious effects of the case nationwide.
Keywords: Kitzmiller, Tammy -- Trials, litigation, etc. Dover Area School District (Dover, Pa.) -- Trials, litigation, etc. Kitzmiller, Tammy. Dover Area School District (Dover, Pa.) Trials -- Pennsylvania -- Dover. Evolution (Biology) -- Study and teaching (Secondary) -- Law and legislation -- Pennsylvania -- Dover (Township) Intelligent design (Teleology) -- Study and teaching (Secondary) -- Law and legislation -- Pennsylvania -- Dover (Township) Trials -- Dover (Pa.) Evolution -- Study and teaching -- Law and legislation. Creationism -- Study and teaching -- Law and legislation. Trials. Pennsylvania -- Dover. Pennsylvania -- Dover (Township)